A spatial development framework for the Northern Inner Cape Town Sub-metropolitan District - Gryzagoridis, Alexia Voula (School of Architecture, Planning and Geomatics, 2014)
In recent times, against the backdrop of a spatially and socially divided city, private development has flourished across the City of Cape Town (CCT), taking advantage of well-serviced, accessible land to generate upmarket residential and business spaces with picturesque vistas. Consequently, the socio-economic disparities characteristic of South African cities continues to shape the CCT, perpetuating the segregation and spatial distortions that originate in modernist philosophy, ultimately affecting the overall city functioning. With this in mind, it is evident that there are major issues in specifying the nature of future development in the CCT. Additionally, from a planning perspective, it is fundamental to ascertain how to optimize land use and development for the benefit of the city at large. The 'northern inner' district of the CCT has emerged, in some ways out of necessity, as a location of high development potential. It comprises both private and state-owned land, including that of the commercial Century City development and Ysterplaat Air Force Base, as well as deep-rooted low to middle income residential areas. The proximity of this site to major movement routes (i.e. the N1 and N7) and economic activities elicits a highly sought after parcel of land. However, it currently lacks coherent structure, resulting in the need for a sound development strategy to direct future growth in this locality. Through an assessment of the complexities of the urban system at the metropolitan scale, as well as an analysis and interpretation of local conditions, this dissertation aims to create a strategic spatial development framework (SDF), underlining the role and potential of the northern inner district of the CCT.